ACTIO PAULIANA LAWSUIT CONCERNING THE TRANSFER OF ASSETS BY INSOLVENT DEBTORS: AN ANALYSIS OF SUPREME COURT DECISION NUMBER 26 PK/PDT.SUS-BANKRUPTCY/2020 - Kacita, Sisillia; Susanti, Erna; Damanik, Amsari (Jambura Journal Civic Education, 2025)
This study seeks to examine the application of the actio pauliana lawsuit concerning the transfer of assets by bankrupt debtors, with a particular focus on Supreme Court Decision Number 26 PK/Pdt.SusBankruptcy/2020. This decision serves as a representation of the legal protection mechanism for creditors within the bankruptcy process. The research employs a normative juridical method, concentrating on the analysis of written legal norms pertinent to the annulment of the debtor's legal actions. The approach includes a statutory analysis to assess the alignment of the decision with Article 1341 of the Civil Code and Article 41 of Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations. Data sources comprise primary data, including laws and regulations, court decisions, and bankruptcy legal documents, while secondary data is derived from literature, scientific journals, academic articles, and expert legal opinions. The findings indicate that in Supreme Court Decision Number 26 PK/Pdt.Sus-Bankruptcy/2020, the debtor's asset transfer was declared null and void as it satisfied all elements of actio pauliana. These elements include the execution of legal actions during the debtor's insolvency, resulting in creditor losses, absence of legal obligations, and lack of good faith by both the debtor and the asset recipient. Consequently, the transferred assets are reinstated to the bankruptcy estate as a means of restoring creditor rights in the debt settlement process. This research affirms that actio pauliana is a crucial instrument in ensuring legal protection for creditors and plays a strategic role in upholding proportional justice, legal certainty, and the integrity of the bankruptcy process in Indonesia.